MANAJEMEN PENDIDIKAN SISTEM GANDA DALAM MENINGKATKAN KOMPETENSI SISWA SMK DI KABUPATEN MALUKU TENGGARA (Studi Kasus di SMK Siwa Lima St. Yoseph Langgur) (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
This research aim to : ( 1) to discribe of implementation of double system education management done in SMK Siwa Five St. Joseph Langgur in the form of activity Prakerin for the rmeningkatkan of student competence, ( 2) to describe the result in double system education management executed by SMK Siwa Five St. Joseph Langgur of during student follow the ctivity Prakerin ( 3) to describe resistance / constraint and also excess met in double system education execution pass the Prakerin executed by SMK Siwa Five St. Joseph Langgur in improving its student competence. The approach used in this research is approach qualitative, the research source data cover is : student following Prakerin, vocational teacher / majors, lead the vocational program / majors, vice headmaster ofhumanity relathion, vice headmaster of curriculum, and headmaster. Data collecting done by perception, observation, and documentation. The result of research show: ( 1) double system education management done by SMK Siwa Five St. Joseph Langgur in the form of Prakerin implicitly have walked but not yet optimal, because still lack of activity synchronization in executed management steps, ( 2) Result obtained in double system education management done by SMK Siwa Five St. Joseph Langgur in the form of Prakerin show result of process of during student follow the Prakerin, while result in object become not yet looked, ( 3) execution of management of system education done by SMK Siwa Five St. Joseph Langgur in Prakerin.